High status of mercury and selenium in false killer whales (Pseudorca crassidens, Owen 1846) stranded on Southern South America: A possible toxicological concern? - Cáceres Saez, Iris; Haro, Daniela; Blank, Olivia; Aguayo Lobo, Anelio; Dougnac, Catherine; Arredondo, Cristóbal; Cappozzo, Humberto Luis; Ribeiro, Sergio (Chemosphere)
The study was carried out to determine Hg and Se concentrations in false killer whales stranded on the Estrecho de Magallanes, Chile, South America. Tissue samples of five mature specimens were analyzed (two females and three males). Mean Hg concentration in liver 1068 (234) μg g−1 dry weight (DW) (standard deviation in parenthesis) was markedly higher than those in kidney 272 (152) μg g−1 DW, lung 423 (325) μg g−1 DW, spleen 725 (696) μg g−1 DW, muscle 118 (94) μg g−1 DW and testicle 18.0 (2.8) μg g−1 DW. Mean Se concentration in liver, 398 (75) μg g−1 DW, was higher than those in kidney 162 (69) μg g−1 DW, lung 128 (84) μg g−1 DW, spleen 268 (245) μg g−1 DW, muscle 47 (38) μg g−1 DW and testicle 25.4 (2.1) μg g−1 DW. Positive correlations were found between Hg and Se molar concentrations in muscle, lung, spleen and kidney. Molar ratio of Se/Hg in liver, lung and muscle were <1, but those in kidney and testicle were markedly >1 suggesting a Se protection against Hg toxicity. In all the examined specimens Hg values exceeded the toxic thresholds defined for hepatic damage in marine mammals, with Se/Hg molar ratios below 1 implying limited protective action of Se. Generally, our results showed that individuals are carrying a significant burden, reflecting a high exposure to this toxic metal. This constitutes the first report on Hg and Se levels for a large subantarctic odontocete in South America region, providing insights into their contamination status and with information to the understanding of possible impacts on wild populations. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Haro, Daniela. Universidad de Chile; Chile. Universidad Santo Tomas; Chile Fil: Blank, Olivia. Clínica Veterinaria Timaukel; Chile. Centro de Rehabilitación de Aves Leñadura Chile Fil: Aguayo Lobo, Anelio. Instituto Antártico Chileno; Chile Fil: ...